Sedimentary Organic Matter Shapes Macrofaunal Communities but Not Benthic Nutrient Fluxes in Contrasting Habitats Along the Northwest Atlantic Continental Margin - Miatta, Marta; Snelgrove, Paul V. R. (Frontiers in Marine Science, 2021)
The heterogeneous topography of continental margins can influence patterns of resource availability and biodiversity in deep-sea sediments, potentially altering ecosystem functioning (e.g., organic matter remineralization). Noting a lack of studies that address the latter, we contrasted spatial patterns and drivers of benthic nutrient fluxes and multiple characteristics of macrofaunal communities in shelf, slope, canyon and inter-canyon sedimentary habitats along the Northwest Atlantic continental margin. Replicate sediment push cores were collected from 10 stations (229–996 m depth), incubated for ∼48 h to estimate fluxes of nitrate, nitrite, ammonium, phosphate, and silicate (as a measure of organic matter remineralization) and subsequently analyzed to characterize macrofaunal communities. We also considered various environmental factors, including sedimentary organic matter quantity and quality, and assessed their influence on fluxes and macrofauna. Comparatively high macrofaunal density and distinct community composition and trait expression characterized Georges Canyon, where elevated sedimentary organic matter suggested important lateral transport mechanisms along this canyon axis, with deposition of organic matter strongly affecting biological communities but not benthic nutrient fluxes. Lower penetration of macrofauna into the sediments, distinct community composition, biological traits, and higher nutrient flux rates characterized inter-canyon habitats compared to slope habitats at similar depths. Within inter-canyons, intermediate to low organic matter suggested hydrodynamic forces inhibiting organic matter deposition, affecting biological and functional processes. The input of fresh phytodetritus to the seafloor was the best predictor of macrofaunal density and diversity and contributed to variation in macrofaunal community composition and biological trait expression, together with latitude, depth, and other measures of organic matter quantity and quality. Benthic nutrient fluxes revealed complex variation, with disproportionate effects of few key macrofaunal taxa, together with bottom water oxygen concentration, and sediment granulometry. Our results suggest a relationship between resource availability and macrofaunal density, diversity, and taxonomic and trait composition, whereas organic matter remineralization exhibited a more complex response, which we suggest reflected variation in hydrodynamics and/or physical disturbance in heterogeneous continental margin habitats.